The Impact of Nationalism of Consumers Loyalty : A Case Study of Multinational Retail Firms in China - Bo, Wu; Hamrila, Abdul Latip; Mahani, Mohammad; Sharizal, Hashim (Scientific Research Publishing, 2023)
Contradictory ideas about China as a country and a state are being marketed to the public by promoting nationalism and transnationalism regarding multinational businesses. Thus, using a case study approach with Multinational Retail Companies in China, this research aims to examine the effect of nationalism on brand allegiance among Chinese customers. This phenomenon has been regarded as a metaphor for China’s uncertainty and fear of its cultural heritage and global capitalism. On the one hand, Chinese commercials peddle pride by highlighting the country’s rich past, current events, and illustrious dynasties. Conversely, Chinese commercials use Western icons and ideals to glamorize their wares. As part of their effort to integrate “Chineseness” with global capitalism, Chinese marketers also peddle a form of nationalism that combines elements of both transnationalism and the traditional nationalist ideology. Nationalism and transnationalism emerge as competing conceptual frameworks for understanding China in an industrialized world characterized by unequal relationships of power between both China and the West. This study shows that the business strategies, ownership structures, years in China, and capital expenditures of U.S. MNCs in China all vary significantly because of trademark royalties. This, in turn, affects how businesses evaluate political risk and decide among available responses to the trade dispute. The research in this paper shows that economic nationalism has a negative impact on the operation of multinational retail enterprises in China. This paper analyzes the factors and ways of influence through case studies. On the one hand, it helps multinational companies to provide suggestions for better localization strategies in China, and on the other hand, it can provide a reference for Chinese enterprises to go global.